2020
DOI: 10.3758/s13421-020-01028-2
|View full text |Cite
|
Sign up to set email alerts
|

Increasing control improves further control, but it does not enhance memory for the targets in a face–word Stroop task

Abstract: Recent research on the dynamics between attentional and memory processes have outlined the idea that applying control in a conflicting situation directly leads to enhanced episodic memory of the processed information. However, in spite of a small subset of studies supporting this claim, the majority of the evidence in the field seems to support the opposite pattern. In this study, we used a face-word Stroop task to enforce different control modes either from trial to trial or in an item-specific manner. Both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…A somewhat related literature has assessed incidental memory for the actual task stimuli in Stroop-type paradigms, with rather mixed results. Here, some studies have shown that participants can better remember incidentally encoded incongruent relative to congruent target stimuli, suggesting that conflict can enhance memory (Davis et al, 2019;Krebs et al, 2015;Ptok et al, 2019;Ptok et al, 2020;, while others have found null results or worse memory for incongruent targets (Jiménez et al, 2020;Ortiz-Tudela et al, 2017). Moreover, there is debate on whether putative memory enhancements may be driven by response conflict or semantic conflict (Muhmenthaler & Meier, 2019;Ptok et al, 2019;Ptok et al, 2020).…”
Section: Subsequent Memory Effectsmentioning
confidence: 97%
“…A somewhat related literature has assessed incidental memory for the actual task stimuli in Stroop-type paradigms, with rather mixed results. Here, some studies have shown that participants can better remember incidentally encoded incongruent relative to congruent target stimuli, suggesting that conflict can enhance memory (Davis et al, 2019;Krebs et al, 2015;Ptok et al, 2019;Ptok et al, 2020;, while others have found null results or worse memory for incongruent targets (Jiménez et al, 2020;Ortiz-Tudela et al, 2017). Moreover, there is debate on whether putative memory enhancements may be driven by response conflict or semantic conflict (Muhmenthaler & Meier, 2019;Ptok et al, 2019;Ptok et al, 2020).…”
Section: Subsequent Memory Effectsmentioning
confidence: 97%
“…In Jiménez et al (2020, Experiment 2), for instance, participants responded to the gender of faces which were repeatedly presented with an overlaid word that could be either congruent or incongruent with the required response (i.e., the words male or female ). As in the present experiments, the authors found clear evidence indicating that the repetition of distracter–target pairs speeded up performance, producing larger congruency effects for those faces which were most frequently paired with a congruent distracter, relative to those faces which were mostly associated with an incongruent distracter.…”
Section: The Interaction Between Conflict and Memory And/or Learningmentioning
confidence: 99%
“…In a replication attempt, Jiménez et al (2020) found no evidence for conflict-enhanced memory. However, they found a memory benefit for incongruent trials following incongruent trials, suggesting that conflict over two successive trials might be necessary to boost target memory.…”
Section: Task Switchingmentioning
confidence: 84%
“…Another line of research investigated the impact of conflict stimuli on subsequent memory performance (Krebs et al, 2015;Rosner et al, 2015a;Jiménez et al, 2020;Muhmenthaler and Meier, 2021a,b). It was suggested that detecting conflicts can enhance target memory (Botvinick et al, 2001(Botvinick et al, , 2004Yeung et al, 2004;Carter and Van Veen, 2007).…”
Section: Task Switchingmentioning
confidence: 99%